History of Uzbek National Dance - Nasiba, Abraykulova; Zebo, Fazlieva; Narziddin, Shermatov; Saida, Zokirova (International Journal of Psychosocial Rehabilitation, 2020)
The article is devoted to the study of the history of Uzbek national dance. The author, noting the ancient origins of the national Uzbek dance, as evidenced by cave paintings. Uzbek folk dances reflect the history and tradition of the ancient people. Dance plays a major role in the life and culture of the people and conveys the experience gained by a person, skills, his nature, social status, and character.